The Use of Animated Cartoon Video in Teaching Writing Descriptive Text for Junior High School Students - KHARIM, NASTA'INUL (RETAIN : Journal of Research in English Language Teaching, 2023)
Human beings produce languages for interacting with others. Both in learning and teaching, learners sometimes have problems in writing paragraph, especially writing descriptive text.  One of the solutions to improve students’ writing is by giving animated cartoon video. This research employs qualitative method with research 8 grade Junior High School Students in Bojonegoro as the subjects. The purpose of the research is to describe the use of animated cartoon video in teaching descriptive text and to know students’ responses toward the use of animated video in teaching descriptive text. The research instruments used are classroom observation and interview. The researcher carried out the observation in 2 meetings. In every meeting, the teacher gave the homework in different cases, the cases were about Donald Duck, Boboboy and Upin Ipin. The result shows that the use of animated video such as Upin Ipin and Donald Duck effectively improve students’ ability in writing descriptive text. Students are able to describe the characters from the animated video completely. Moreover, students are happy when animated videos are used as a media in teaching descriptive text. The used of animated cartoon that commonly spoken was succeeded. It might be concluded  that the teaching animated cartoon  for descriptive text could support learners’ thought to write descriptive text vividly.